Digital Literacy Program for Mahasantri at Perguruan Tinggi Keagamaan Islam (PTKI) Metro City in Supporting of Creative Economy - Uswatun Hasanah; Marzia Khatan Smita; Suhono (CV. Creative Tugu Pena, 2025)
The rapid growth of the creative economy is often hampered by a mismatch between the quality of human resources and the digital literacy of younger generations. This study implements a Digital Literacy Assistance Program for Mahasantri at Perguruan Tinggi Keagamaan Islam (PTKI) in Metro City, aiming to empower them as drivers of the creative economy. Utilizing the Asset-Based Community Development (ABCD) approach, the program leverages various assets, including individual skills, natural resources, and existing infrastructure. The results show that participants acquired critical digital knowledge and skills, enabling them to effectively use e-commerce platforms, expand their market reach, and enhance sales performance. Notably, the program led to a 20% increase in market reach and improvements in product branding strategies. It also raised awareness among Mahasantri about the potential of the creative economy, helping them recognize their own creative capacities and the opportunities available. This study highlights the importance of targeted digital literacy training in fostering economic empowerment and underscores the need for continued support in this area